Public space in the poetry of Edgardo Antonio Vigo: the señalamientos - Bugnone, Ana Liza (Revista do Colóquio, 2022)
Within a broader poetics, Vigo developed a series of actions that he called señalamientos. This article will address the meaning of these actions carried out in public space between 1968 and 1973. If Vigo proposed a new configuration of art through public participation and the unstable presence of the author, as well as the abandonment of the canonical practices of circulating works of art in museums, awards and galleries, the señalamientos were a more or less stable amalgamated form of this program. The presence of these elements becomes evident when analyzing the characteristics of each one, their relationship with the environment in which they were made and the repercussions they had. Likewise, Vigo theorized about them, defined them and placed them within the framework of his poetry, while at the same time trying out responses to the political events of the moment.